2021
DOI: 10.1002/capr.12490
|View full text |Cite
|
Sign up to set email alerts
|

Client–therapist closeness–distance dynamics as a pathway for understanding changes in the alliance during psychodynamic therapy

Abstract: This study examines how changes in clients’ and their therapists’ perceptions of the therapeutic distance relate to changes in their reported alliance. Alliance is commonly measured using self‐report questionnaires that provide information regarding the partners’ bond and collaboration, but do not reflect the interactions or events underlining them. We developed the Observer Version of the Therapeutic Distance Scale (TDS‐O; Egozi et al., 2020) to assess components of the therapeutic relationship, including clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The TDS-O enables us to follow congruence and incongruence between patient and therapist experiences regarding their proximity, and thus has the potential to contribute to therapist ability to attune to patient emotional needs at the specific moment (49). The second study (47), demonstrated significant relations between the TDS-O and the therapeutic alliance. Patient and therapist decrease in their sense that the partner was too distant correlated with increase in the alliance, as did therapist decrease in the sense that the patient was too close.…”
Section: The Therapeutic Distance Scaleobserver Version (Tds-o)mentioning
confidence: 89%
See 1 more Smart Citation
“…The TDS-O enables us to follow congruence and incongruence between patient and therapist experiences regarding their proximity, and thus has the potential to contribute to therapist ability to attune to patient emotional needs at the specific moment (49). The second study (47), demonstrated significant relations between the TDS-O and the therapeutic alliance. Patient and therapist decrease in their sense that the partner was too distant correlated with increase in the alliance, as did therapist decrease in the sense that the patient was too close.…”
Section: The Therapeutic Distance Scaleobserver Version (Tds-o)mentioning
confidence: 89%
“…Following Mallinckrodt and Jeong's (45) model, and taking a relational perspective (46), the TDS-O was developed to track the unique dyadic dance between patient and therapist, focusing on the closeness-distance experiences of both patients and therapists. The TDS-O expanded the TDS by creating an observer-narrative-based version [TDS-O; (20,21,47)], which enables the researcher to follow both the patient's and the therapist's experiences through their descriptions of their interactions with each other. The narratives told by patients and therapists provide a window into subjective significant moments at different phases of therapy by coding the narratives on the four scales of the TDS-O.…”
Section: The Therapeutic Distance Scaleobserver Version (Tds-o)mentioning
confidence: 99%
“…The therapists’ lasting ambivalence toward the remote format in our study raises the issue of patient–therapist matching. How to optimize the distance is dependent on the patient–therapist matching in each individual case (cf., Egozi et al, 2022; Werbart et al, 2018). As expressed by the therapists in our study, the distance–closeness regulation in remote encounters requires new and advanced therapeutic skills.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…The idea of therapeutic distance can be traced back to the work of Mallinckrodt (2010), Mallinckrodt et al (2015) and is defined as therapists' ability to regulate themselves based on their client's emotional needs during a session. Using therapeutic distance increases the scaffolding of the therapeutic alliance, as it creates a dynamic of closeness and distance between client and therapist (Egozi et al, 2021). Tremain et al (2020) suggest that for people with serious mental illnesses, therapeutic alliance can be fostered through digital interventions (technology-based interventions providing information and support, as well as emotional, decisional, behavioral, and neurocognitive therapy for physical and mental health problems), but that such an alliance may have unique characteristics that have yet to be confirmed in digital settings.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of therapeutic distance can be traced back to the work of Mallinckrodt (2010), Mallinckrodt et al (2015) and is defined as therapists' ability to regulate themselves based on their client's emotional needs during a session. Using therapeutic distance increases the scaffolding of the therapeutic alliance, as it creates a dynamic of closeness and distance between client and therapist (Egozi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%